Klasifikasi Data Nasabah Asuransi Dengan Menggunakan Metode Naive Bayes - Dyah Arumatica Novilla; Rito Goejantoro; Fidia Deny Tisna Amijaya (EKSPONENSIAL, 2019)
Classification is the logical grouping of objects according to the characteristics of their similarities. Naive Bayes is a method for predicting future opportunities based on past experiences. This study discusses the classification of insurance customer data of PT. Prudential Life Branch of Samarinda in 2017. With the aim to know whether the method of Naive Bayes can classify data of insurance customers of PT. Prudential Life in 2017 using the R program and to determine the accuracy of the results of data testing I and data testing II. As a result, Naive Bayes method can classify data of insurance customers of PT. Prudential Life with 80% accuracy for 25 data testing I and 74.67% for 75 data testing II.